Solvent-free composite artificial leather capable of absorbing stripes for sofa and preparation method of solvent-free composite artificial leather

By introducing titanium-aluminum hydrotalc nanoparticles and silicon modifiers into solvent-free composite artificial leather, combined with solvent-free polyurethane, the shortcomings of artificial leather in terms of texture absorption, wear resistance and aging resistance are solved, and high-performance and environmentally friendly absorbable solvent-free composite artificial leather for sofas are achieved.

CN119593228APending Publication Date: 2025-03-11ZHEJIANG HEXIN NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411787988.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing solvent-free composite artificial leather has shortcomings in terms of texture absorption, wear resistance and aging resistance, and it is difficult to meet environmental protection and performance requirements.

Method used

Titanium-aluminum hydrotalcite nanoparticles and silicon modifiers are used to combine with solvent-free polyurethane to form a surface layer, and the texture absorption and physical and mechanical properties of artificial leather are improved through the introduction of titanium-aluminum hydrotalcite nanoparticles.

Benefits of technology

It significantly improves the texture absorption effect, wear resistance and aging resistance of artificial leather, while reducing the solvent residue to meet environmental protection requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005174582960000081
    Figure BDA0005174582960000081
  • Figure BDA0005174582960000092
    Figure BDA0005174582960000092
  • Figure BDA0005174582960000093
    Figure BDA0005174582960000093
Patent Text Reader

Abstract

The invention discloses a stripe-absorbable solvent-free composite artificial leather for sofas and a preparation method thereof. According to the technical scheme, the fabric sequentially comprises a surface layer, an attaching layer and a base fabric layer, the base cloth layer is microfiber base cloth made of microfiber through carding and needling; the surface layer comprises the following components in parts by weight: 10-90 parts of titanium aluminum hydrotalcite nanoparticles; 10 to 90 parts of solvent-free polyurethane; 1-10 parts of a silicon modifier; the mass ratio of the titanium aluminum hydrotalcite nanoparticles to the solvent-free polyurethane is (10: 90)-(90: 10); the silicon modifier is formed by mixing a silane coupling agent and ethanol according to the mass ratio of 1: (4-9); the silane coupling agent is one or more of gamma-mercaptopropyltrimethoxysilane, gamma-aminopropyltriethoxysilane, vinyl trimethoxysilane, trimethylethoxysilane, methyl trichlorosilane, dimethyl diethoxysilane, dimethyl dichlorosilane and trimethylchlorosilane. The synthesized artificial leather is good in grain absorption effect, environment-friendly, folding-resistant and wear-resistant.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of artificial leather, in particular to a grain-absorbable solvent-free composite artificial leather for sofas and a preparation method thereof. Background Art

[0002] In recent years, with the enhancement of environmental awareness and the advancement of science and technology, solvent-free lamination technology has been gradually applied to the manufacture of artificial leather. Solvent-free lamination technology does not use organic solvents, which reduces environmental pollution and improves the environmental performance and safety of artificial leather. However, how to further improve the grain absorption, wear resistance and aging resistance of artificial leather on the basis of solvent-free lamination has become a problem that needs to be solved in the current artificial leather manufacturing field.

[0003] Therefore, it is necessary to provide a solvent-free composite artificial leather with absorbable grain for sofa and a preparation method thereof. Summary of the invention

[0004] In view of the above problems, the present invention provides a solvent-free composite artificial leather with absorbent grain for sofas and a preparation method thereof that overcomes the above problems or at least partially solves the above problems. The prepared artificial leather has the characteristics of wear resistance, aging resistance, and good absorbent grain effect, and can effectively reduce the residual solvent in the artificial leather, thereby meeting environmental protection requirements.

[0005] Specifically, the present invention provides a solvent-free composite artificial leather with absorbable grain for sofas, which adopts the following technical scheme: a solvent-free composite artificial leather with absorbable grain for sofas, which comprises a surface layer, a laminating layer and a base fabric layer in sequence; the base fabric layer is a microfiber base fabric made of microfibers by combing and needle punching; the surface layer comprises the following components in parts by weight:

[0006] 10-90 parts of titanium aluminum hydrotalcite nanoparticles;

[0007] 10-90 parts of solvent-free polyurethane;

[0008] 1-10 parts of silicon modifier;

[0009] Among them, the mass ratio of the titanium aluminum hydrotalcite nanoparticles to the solvent-free polyurethane is 10:90-90:10; the silicon modifier is prepared by mixing a silane coupling agent and ethanol in a mass ratio of 1:(4-9); the silane coupling agent is one or more combinations of γ-mercaptopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, vinyltrimethoxysilane, trimethylethoxysilane, methyltrichlorosilane, dimethyldiethoxysilane, dimethyldichlorosilane, and trimethylchlorosilane.

[0010] By adopting the above technical scheme, through the introduction of titanium aluminum hydrotalcite nanoparticles, the artificial leather has excellent grain absorption performance, can simulate the texture and pattern of various natural leathers, improve the texture and aesthetics of the artificial leather, enhance the hardness and wear resistance of the coating, so that the artificial leather of the present invention is not easy to wear and age during long-term use. Silicon modifier and titanium aluminum hydrotalcite are introduced into solvent-free polyurethane to improve the degree of bonding between polyurethane and base fabric and improve physical and mechanical properties. In addition, the introduction of titanium aluminum hydrotalcite nanoparticles can give the artificial leather good flame retardant properties, and its layered structure can also enhance the material's adsorption performance of harmful gases such as indoor VOCs, so that the obtained artificial leather can have excellent wear resistance and folding resistance, grain absorption and environmental protection.

[0011] Preferably, the titanium aluminum hydrotalcite nanoparticles are prepared by the following steps:

[0012] 1) Weigh titanium salt and aluminum salt in a molar ratio of (2-4.5):1 and dissolve them in 1 / 2 amount of deionized water to obtain solution A;

[0013] 2) weighing 1 to 10 times the molar amount of titanium ions in the titanium salt, dissolving the alkali solution in the remaining 1 / 2 amount of deionized water, and stirring to dissolve to obtain solution B;

[0014] 3) Mixing solution B and solution A at 20-100° C. and adjusting the pH to obtain a white suspension with a pH between 5.5 and 10;

[0015] 4) centrifugally separating the product, and drying it at 70-210° C. for 2-48 hours to obtain white titanium aluminum hydrotalcite;

[0016] 5) The dried titanium aluminum hydrotalcite is subjected to ball milling treatment to obtain titanium aluminum hydrotalcite nanoparticles with a particle size of 2 to 100 μm.

[0017] Preferably, the titanium salt is Ti(SO4)2, Ti(S2O7)2, TiO(SO4), Ti4O5(SO4)3, Ti7O 13 (SO4), Ti2O3(SO 4) , at least one of H2TiO3, TiCl4, TiOCl2, TiBr4, TiI4, TiF4, K2TiO(C2O4)2·2H2O, K2TiO(SO4)2, Ti3(PO4)4, Na2TiO3, and CaTiO3;

[0018] The aluminum salt is at least one of AlCl3, Al2(SO4)3, Al(NO3)3, Al2(CO3)3, Al(OH)3, AlF3, AlBr3, AlI3, Al(ClO4)3, AlH(SO4)2, NaAlO2, KAlO2, (NH4)AlO2, KAl(SO4)2·12H2O, NH4AlCl3, (NH4)Al(SO4)2·12H2O, (NH4)3Al(PO4)3, and NaAlO2·2H2O.

[0019] More preferably, the titanium salt used is TiCl4 or TiF4, and the aluminum salt used is Al2(SO4)3 or Al(NO3)3. The drying temperature is 150°C.

[0020] Preferably, the solvent-free polyurethane is composed of material A and material B, wherein material A includes the following components in parts by weight: 30-90 parts of a polyol mixture, 1-10 parts of a chain extender, 0.2-0.3 parts of a catalyst, 1-5 parts of a filler, and 0.1-1 parts of a UV additive; wherein the polyol mixture includes 10-80 parts of a polymer polyol, 20-65 parts of amino polyethylene glycol carboxyls, and 0.3-0.5 parts of a sorbitan fatty acid ester; material B is an isocyanate prepolymer obtained by polymerizing the polyol mixture with isocyanate, and has an -NCO content of 5% to 35%, and the polyol mixture is the same as that used in material A; the mass ratio of material A to material B is (1.5-5.5):1.

[0021] Preferably, in the material A, the polymer polyol is at least one of polytetramethylene oxide propylene glycol, polyoxypropylene glycol, polytetramethylene glycol, polybutadiene polyol, polycarbonate polyol, and polycaprolactone diol; the chain extender is at least one of diethanolamine, ethylenediamine, diethylaminoethanol, 3,3-dichloro-4,4-diaminodiphenylmethanediamine, triethylenetetramine, diethylenetriamine, and N-isopropylethylenediamine; and the filler is at least one of cellulose, diatomaceous earth, talc, polyacrylate, corundum, quartz sand, wollastonite powder, and flame retardant.

[0022] Preferably, in the material B, the isocyanate is at least one of p-1,4-methylxylylene diisocyanate, isophorone diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, tetramethyl-m-xylylene diisocyanate and hexamethylene diisocyanate.

[0023] More preferably, the polymer polyol used is at least one of polybutadiene polyol and polycaprolactone diol, and the isocyanate in the material B is at least one of dicyclohexylmethane-4,4'-diisocyanate and tetramethyl-m-xylylene diisocyanate.

[0024] Preferably, the solvent-free polyurethane further comprises 0.1-0.5 parts of itaconic anhydride copolymer microspheres.

[0025] The present invention also provides a method for preparing the above-mentioned solvent-free composite artificial leather with absorbable grain for sofas, which adopts the following technical scheme:

[0026] A method for preparing a solvent-free composite artificial leather with absorbable grain for sofas comprises the following steps:

[0027] Step 1: Preparation of solvent-free polyurethane

[0028] In parts by weight, a polyol mixture, a chain extender, a catalyst, a filler and a UV additive are stirred and mixed uniformly at 20-50° C. to obtain the material A; the polyol mixture is polymerized with isocyanate at 80-120° C. to obtain an isocyanate prepolymer having an -NCO content of 5% to 35%, i.e., material B; and material A and material B are mixed to obtain a solvent-free polyurethane;

[0029] Step 2:

[0030] The titanium aluminum hydrotalcite nanoparticles and the solvent-free polyurethane are uniformly mixed to obtain a hydrotalcite solvent-free component;

[0031] The silane coupling agent is added to ethanol, mixed evenly, and then lactic acid is added to adjust the pH to 2-6 to obtain a silicon modifier;

[0032] Adding a silicon modifier to the hydrotalcite solvent-free component and mixing them evenly to obtain a silicon-based hydrotalcite solvent-free composite material, wherein the mass ratio of the silicon modifier to the hydrotalcite solvent-free component is 1:99 to 10:90;

[0033] Step 3:

[0034] The silicon-based hydrotalcite solvent-free composite material is coated on the release paper, and dried at 110-130°C for 2-3 minutes to form a surface layer, and then a laminating adhesive is applied on the side of the surface layer away from the release paper to form a laminating layer, and the side of the laminating layer away from the surface layer is combined with the base fabric layer, and dried at 80-120°C for 2-5 minutes to obtain a finished product;

[0035] Step 4:

[0036] The finished product and the release paper are separated and rolled up through a winding guide roller device, and a grain absorbing device is used to carry out a grain absorbing operation on the obtained artificial leather to obtain the grain absorbing solvent-free composite artificial leather for sofas.

[0037] In summary, the beneficial effects of the present invention are:

[0038] The present invention introduces silane coupling agent and titanium aluminum hydrotalcite into solvent-free composite technology, which can improve the interface bonding performance between the solvent-free component and the base fabric, thereby improving the bonding degree between the polyurethane and the base fabric and improving the physical and mechanical properties. The introduction of titanium aluminum hydrotalcite nanoparticles gives the artificial leather good flame retardant properties, and its layered structure can also enhance the material's adsorption performance for indoor VOCs and other harmful gases, improve the grain absorption effect of the artificial leather, and achieve improvements in environmental protection, grain absorption, wear resistance, and aging resistance of the artificial leather. DETAILED DESCRIPTION

[0039] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is described in detail below in conjunction with specific examples, comparative examples and experimental data. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. The raw materials, reagents and equipment involved in the embodiments of the present invention, unless otherwise specified, can all be obtained through commercial channels.

[0040] Preparation Example

[0041] Preparation Example 1: Preparation of Titanium-Aluminum Hydrotalcite Nanoparticles

[0042] The preparation method is as follows: weigh 570.7 g TiCl4 and 213 g Al(NO3)3 and dissolve them in 2 L deionized water to obtain solution A with a cation concentration of 3 mol / L;

[0043] According to Ti 4+ Weigh 3 times the molar amount of KOH, dissolve it in 2 L of deionized water, and stir to dissolve to obtain solution B;

[0044] At 55°C, solution B and solution A were mixed and adjusted to obtain a white suspension with a pH of 6. The white suspension was then centrifuged to separate the solid and the post-reaction solution, and dried at 150°C for 24 hours to obtain white titanium aluminum hydrotalcite. The dried titanium aluminum hydrotalcite was ball milled with the following ball milling parameters: ball milling time 15 minutes, ball milling speed 120 rpm. Titanium aluminum hydrotalcite nanoparticles with a particle size of 33 μm were obtained.

[0045] Preparation Example 2: Preparation of Silicon Modifier

[0046] The silane coupling agent is a combination of γ-mercaptopropyltrimethoxysilane and γ-aminopropyltriethoxysilane in a mass ratio of 1:1.

[0047] The preparation is as follows: 18 parts of silane coupling agent are added to 82 parts of ethanol, and after mixing evenly, lactic acid is added to adjust the pH to 4 to obtain a silicon modifier.

[0048] Preparation Example 3: The difference between this Preparation Example and Preparation Example 2 is that the mass ratio of the silane coupling agent to ethanol is 10:90.

[0049] Preparation Example 4: The difference between this Preparation Example and Preparation Example 2 is that the mass ratio of the silane coupling agent to ethanol is 20:80.

[0050] Preparation Example 5: Preparation of itaconic anhydride copolymer microspheres

[0051] 5.6 parts of itaconic anhydride monomer, 4.3 parts of vinyl acetate and 0.8 parts of azodiisopropylimidazoline hydrochloride were added to a container, ultrasonically dissolved in 70 mL of butyl acetate, and N2 was passed for 30 minutes. The container was then placed in an 80°C oil bath and reacted in a N2 atmosphere for 6 hours. After the reaction, the product was centrifuged for 10 minutes, the supernatant was poured off, and the precipitate was washed with toluene solvent, and then washed with petroleum ether. The centrifuged product was dried in a vacuum oven at 100°C for 10 minutes to obtain itaconic anhydride-vinyl acetate copolymer microspheres.

[0052] Example

[0053] Embodiment 1:

[0054] The invention discloses a solvent-free composite artificial leather with absorbable grain for sofas, which comprises a surface layer, a laminating layer and a base fabric layer in sequence.

[0055] In parts by weight, the surface layer includes 15 parts of titanium aluminum hydrotalcite nanoparticles, 85 parts of solvent-free polyurethane and 5 parts of silicon modifier.

[0056] The bonding layer is water-based bonding adhesive.

[0057] The base fabric layer is a microfiber base fabric made of microfibers by carding and needle punching, wherein the single filament fineness of the microfibers is 0.3 dtex.

[0058] The method for preparing the above-mentioned solvent-free composite artificial leather with absorbable grain for sofa comprises the following steps:

[0059] Step 1, Preparation of solvent-free polyurethane

[0060] Preparation of material A: dehydrate polybutadiene polyol under reduced pressure to obtain dehydrated polybutadiene polyol; take 20 parts of dehydrated polybutadiene polyol, 25 parts of amino polyethylene glycol carboxyl, and 0.35 parts of sorbitan fatty acid ester to obtain a polyol mixture. Take 50 parts of the polyol mixture, add 0.25 parts of N,N,N',N'-tetramethylalkylenediamine, 2 parts of diethanolamine, 3 parts of quartz sand and 0.2 parts of UV-531 anti-aging additive, heat to 35°C and mix evenly to obtain material A;

[0061] Preparation of material B: 1.06 parts of dicyclohexylmethane-4,4'-diisocyanate were added to 10 parts of the polyol mixture, and the polymerization reaction was carried out at 120°C for 10 minutes. The -NCO content of the product was titrated to find that it was 7%, and the product isocyanate prepolymer, i.e. material B, was obtained;

[0062] Material A and material B are mixed to obtain solvent-free polyurethane, wherein the mass ratio of material A to material B is 3.5:1.

[0063] Step 2, preparation of hydrotalcite solvent-free component

[0064] Take 15 parts of the titanium aluminum hydrotalcite nanoparticles obtained in Preparation Example 1 and 85 parts of solvent-free polyurethane, and mechanically stir for 20 minutes to mix them evenly to obtain a hydrotalcite solvent-free component.

[0065] The silicon modifier obtained in Preparation Example 2 was added to the hydrotalcite solvent-free component and mixed evenly to obtain a silicon-based hydrotalcite solvent-free composite material, wherein the mass ratio of the silicon modifier to the hydrotalcite solvent-free component was 5:95.

[0066] Step 3, Preparation of synthetic leather

[0067] The silicon-based hydrotalcite solvent-free composite material is coated on the release paper as the surface layer resin, and dried at 130°C for 3 minutes. A water-resistant laminating adhesive is coated on the release paper coated with the surface layer, and a microfiber base cloth is laminated and dried at 120°C for 5 minutes. After drying, the paper and leather are separated to obtain the finished product.

[0068] Step 4, post-processing

[0069] The finished product and the release paper are separated and rolled up through a winding guide roller device, and a grain absorbing device is used to perform a grain absorbing operation. The grain absorbing process parameters are: 190° C., -0.07 MPa, and 20 m / min, to obtain the grain absorbing solvent-free composite artificial leather for the sofa.

[0070] Embodiment 2:

[0071] The difference from Example 1 is that the mass ratio of the titanium aluminum hydrotalcite nanoparticles to the solvent-free polyurethane is 10:90.

[0072] Embodiment 3:

[0073] The difference from Example 1 is that the mass ratio of the titanium aluminum hydrotalcite nanoparticles to the solvent-free polyurethane is 90:10.

[0074] Embodiment 4:

[0075] The difference from Example 1 is that the mass ratio of material A to material B in the solvent-free polyurethane is 1.5:1.

[0076] Embodiment 5:

[0077] The difference from Example 1 is that the mass ratio of material A to material B in the solvent-free polyurethane is 5.5:1.

[0078] Embodiment 6:

[0079] The difference from Example 1 is that the silicon modifier is prepared by Preparation Example 3.

[0080] Embodiment 7:

[0081] The difference from Example 1 is that the silicon modifier is prepared by Preparation Example 4.

[0082] Embodiment 8:

[0083] The difference from Example 1 is that in the surface layer, the ratio of the silicon modifier to the hydrotalcite solvent-free component is 1:99.

[0084] Embodiment 9:

[0085] The difference from Example 1 is that in the surface layer, the ratio of the silicon modifier to the hydrotalcite solvent-free component is 10:90.

[0086] Embodiment 10:

[0087] The difference from Example 1 is that the surface layer further comprises 0.2 parts of itaconic anhydride copolymer microspheres.

[0088] Comparative Example

[0089] Comparative Example 1: The difference from Example 1 is that the surface layer does not include a silicon modifier.

[0090] Comparative Example 2: The difference from Example 1 is that the surface layer does not include titanium aluminum hydrotalcite and silicon modifier.

[0091] Comparative Example 3: The difference from Example 1 is that in the surface layer, the mass ratio of titanium aluminum hydrotalcite nanoparticles to solvent-free polyurethane is 95:5.

[0092] Comparative Example 4: The difference from Example 1 is that in the surface layer, the mass ratio of the silicon modifier to the hydrotalcite solvent-free component is 15:85.

[0093] Performance Testing

[0094] Experiment 1: According to QB / T2888-2007, the tensile load, elongation at break, elongation under fixed load and tearing load of leather were tested.

[0095] Experiment 2, wear resistance test: GT-7012-T TABER wear tester was used, the rotating platform rotated at a speed of 60r / min, the support pressure was increased by adding weights to increase the load on the sample, and the friction wheel was driven to roll through the rotating platform to form wear marks. After the specified number of friction circles, the sample surface wear and color change were graded and evaluated. Samples of the embodiments and comparative examples were taken for testing: circular test samples with a diameter of 106mm were taken from the finished artificial leather products of embodiments 1-10 and comparative examples 1-4, and a circular hole with a diameter of 6mm was formed in the center.

[0096] Experiment 3, folding resistance test: Use a leather flexural resistance tester. Fold the test surface of the leather sample inwards, so that the two long sides are together, clamp the folded sample, stretch it vertically and put it into the clamp. The flexing angle of the clamp is 22°, the flexing frequency is 100 times / min, and the machine stops automatically after the preset flexing times. After the test is completed, take out the sample, fold it in the opposite direction along the longitudinal direction, check and record the degree of damage of the flexed part to judge the folding resistance.

[0097] Experiment 4: Test the yellowing resistance of leather according to QB / T2888-2007.

[0098] Test results

[0099] The test results of the properties of the artificial leather prepared in Examples 1-10 and Comparative Examples 1-4 are shown in Table 1-3.

[0100] Table 1 Performance test table of embodiments 1-5

[0101]

[0102]

[0103] Table 2 Performance test table of Examples 6-10

[0104]

[0105] Table 3 Performance test table of comparative examples 1-4

[0106]

[0107]

[0108] It can be seen from Tables 1-3 that the wear resistance and folding resistance of Examples 1-10 of the present application are better than those of Comparative Examples 1-5. This is because the present application introduces titanium aluminum hydrotalcite nanoparticles and silicon modifiers to form a surface layer in combination with solvent-free polyurethane, and each component can play its respective role well, so that the finished synthetic leather can achieve better physical and mechanical properties.

[0109] Comparing Examples 1-3 with Comparative Examples 1 and 4, it can be seen that the addition of silicon modifiers in the surface layer and the limited amount of silicon modifiers have a greater effect on its tensile, folding and wear resistance. The wear resistance and durability of artificial leather can be enhanced by adjusting the proportion. Comparing Examples 1, 4, and 5 with Comparative Examples 2 and 3, it can be seen that without adding titanium aluminum hydrotalcite and silicon modifiers, only using solvent-free polyurethane as the surface layer, its tensile and folding resistance are reduced. At the same time, the amount of titanium aluminum hydrotalcite added will also affect the final mechanical properties of synthetic leather. Among them, in the case of Comparative Example 2, the synthetic leather product cannot be well made into a texture pattern.

[0110] By comparing Example 1 with Examples 6-9, it can be seen that the amount of silicon modifier used in the present application and the mixing ratio of the silane coupling agent and ethanol therein have a great influence on the hydrotalcite solvent-free component, and the physical and mechanical properties and molding effect of the final synthetic leather can be improved under the limited preferred ratio. By comparing Example 1 with Example 10, it can be seen that adding an appropriate amount of itaconic anhydride copolymer microspheres can work together with titanium aluminum hydrotalcite to enhance the adsorption, so that the tensile and folding resistance of the surface layer are better. At the same time, under the ratio of Example 10, the synthetic leather product can be more easily operated to absorb the grain, and the absorption grain molding effect is better visible to the naked eye.

[0111] The embodiments described above are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention, and should all be included in the protection scope of the present invention.

Claims

1. A solvent-free composite artificial leather with absorbable grain for sofa, characterized in that: It comprises a surface layer, a bonding layer and a base fabric layer in sequence; the base fabric layer is a microfiber base fabric made of microfibers by carding and needle punching; the surface layer comprises the following components in parts by weight: 10-90 parts of titanium aluminum hydrotalcite nanoparticles; 10-90 parts of solvent-free polyurethane; 1-10 parts of silicon modifier; Among them, the mass ratio of the titanium aluminum hydrotalcite nanoparticles to the solvent-free polyurethane is 10:90-90:10; the silicon modifier is prepared by mixing a silane coupling agent and ethanol in a mass ratio of 1:(4-9); the silane coupling agent is one or more combinations of γ-mercaptopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, vinyltrimethoxysilane, trimethylethoxysilane, methyltrichlorosilane, dimethyldiethoxysilane, dimethyldichlorosilane, and trimethylchlorosilane.

2. The solvent-free composite artificial leather with absorbable grain for sofa according to claim 1, characterized in that: The titanium aluminum hydrotalcite nanoparticles are prepared by the following steps: 1) Weigh titanium salt and aluminum salt in a molar ratio of (2-4.5):1 and dissolve them in 1 / 2 amount of deionized water to obtain solution A; 2) weighing 1 to 10 times the molar amount of titanium ions in the titanium salt, dissolving the alkali solution in the remaining 1 / 2 amount of deionized water, and stirring to dissolve to obtain solution B; 3) Mixing solution B and solution A at 20-100° C. and adjusting the pH to obtain a white suspension with a pH between 5.5 and 10; 4) centrifugally separating the product, and drying it at 70-210° C. for 2-48 hours to obtain white titanium aluminum hydrotalcite; 5) The dried titanium aluminum hydrotalcite is subjected to ball milling treatment to obtain titanium aluminum hydrotalcite nanoparticles with a particle size of 2 to 100 μm.

3. The solvent-free composite artificial leather with absorbable grain for sofa according to claim 2, characterized in that: Titanium salts are Ti(SO4)2, Ti(S2O7)2, TiO(SO4), Ti4O5(SO4)3, Ti7O 13 (SO4), Ti2O3(SO 4) , H2TiO3, TiCl4, TiOCl2, TiBr4, TiI4, TiF4, K2TiO(C2O4)2·2H2O, K2TiO(SO4)2, Ti3(PO4)4, Na2TiO3, and CaTiO3; the aluminum salt is at least one of AlCl3, Al2(SO4)3, Al(NO3)3, Al2(CO3)3, Al(OH)3, AlF3, AlBr3, AlI3, Al(ClO4)3, AlH(SO4)2, NaAlO2, KAlO2, (NH4)AlO2, KAl(SO4)2·12H2O, NH4AlCl3, (NH4)Al(SO4)2·12H2O, (NH4)3Al(PO4)3, and NaAlO2·2H2O.

4. The solvent-free composite artificial leather with absorbable grain for sofa according to claim 3, characterized in that: The titanium salt used is TiCl4 or TiF4, the aluminum salt used is Al2(SO4)3 or Al(NO3)3; the drying temperature is 150°C.

5. The solvent-free composite artificial leather with absorbable grain for sofa according to claim 1, characterized in that: The solvent-free polyurethane is composed of material A and material B, wherein material A comprises the following components in parts by weight: 30-90 parts of a polyol mixture, 1-10 parts of a chain extender, 0.2-0.3 parts of a catalyst, 1-5 parts of a filler, and 0.1-1 parts of a UV additive; wherein the polyol mixture comprises 10-80 parts of a polymer polyol, 20-65 parts of amino polyethylene glycol carboxyls, and 0.3-0.5 parts of a sorbitan fatty acid ester; material B is an isocyanate prepolymer obtained by polymerizing the polyol mixture with isocyanate, and has an -NCO content of 5% to 35%, and the polyol mixture is the same as that used in material A; the mass ratio of material A to material B is (1.5-5.5):

1.

6. The solvent-free composite artificial leather with absorbable grain for sofa according to claim 5, characterized in that: In the material A, the polymer polyol is at least one of polytetramethylene oxide propylene glycol, polyoxypropylene glycol, polytetramethylene glycol, polybutadiene polyol, polycarbonate polyol, and polycaprolactone diol; the chain extender is at least one of diethanolamine, ethylenediamine, diethylaminoethanol, 3,3-dichloro-4,4-diaminodiphenylmethanediamine, triethylenetetramine, diethylenetriamine, and N-isopropylethylenediamine; and the filler is at least one of cellulose, diatomaceous earth, talc, polyacrylate, corundum, quartz sand, wollastonite powder, and flame retardant.

7. The solvent-free composite artificial leather with absorbable grain for sofa according to claim 6, characterized in that: In the material B, the isocyanate is at least one of p-1,4-methylxylylene diisocyanate, isophorone diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, tetramethyl-m-xylylene diisocyanate and hexamethylene diisocyanate.

8. The solvent-free composite artificial leather with absorbable grain for sofa according to claim 7, characterized in that: The polymer polyol used is at least one of polybutadiene polyol and polycaprolactone diol, and the isocyanate in the material B is at least one of dicyclohexylmethane-4,4'-diisocyanate and tetramethyl meta-xylylene diisocyanate.

9. The solvent-free composite artificial leather with absorbable grain for sofa according to claim 1, characterized in that: The solvent-free polyurethane further comprises 0.1-0.5 parts of itaconic anhydride copolymer microspheres.

10. The method for preparing the solvent-free composite artificial leather with absorbable grain for sofas according to any one of claims 1 to 9, characterized in that: The following steps are involved: Step 1: Preparation of solvent-free polyurethane In parts by weight, a polyol mixture, a chain extender, a catalyst, a filler and a UV additive are stirred and mixed uniformly at 20-50° C. to obtain the material A; the polyol mixture is polymerized with isocyanate at 80-120° C. to obtain an isocyanate prepolymer having an -NCO content of 5% to 35%, i.e., material B; and material A and material B are mixed to obtain a solvent-free polyurethane; Step 2: The titanium aluminum hydrotalcite nanoparticles and the solvent-free polyurethane are uniformly mixed to obtain a hydrotalcite solvent-free component; The silane coupling agent is added to ethanol, mixed evenly, and then lactic acid is added to adjust the pH to 2-6 to obtain a silicon modifier; Adding a silicon modifier to the hydrotalcite solvent-free component and mixing them evenly to obtain a silicon-based hydrotalcite solvent-free composite material, wherein the mass ratio of the silicon modifier to the hydrotalcite solvent-free component is 1:99 to 10:90; Step 3: The silicon-based hydrotalcite solvent-free composite material is coated on the release paper, and dried at 110-130°C for 2-3 minutes to form a surface layer, and then a laminating adhesive is applied on the side of the surface layer away from the release paper to form a laminating layer, and the side of the laminating layer away from the surface layer is combined with the base fabric layer, and dried at 80-120°C for 2-5 minutes to obtain a finished product; Step 4: The finished product and the release paper are separated and rolled up through a winding guide roller device, and a grain absorbing device is used to carry out a grain absorbing operation on the obtained artificial leather to obtain the grain absorbing solvent-free composite artificial leather for sofas.